Anisotropic thermal expansion of the acetylene–ammonia co‐crystal under Titan's conditions. Issue 6 (20th November 2020) - Vu, Tuan H.; Maynard-Casely, Helen E.; Cable, Morgan L.; Hodyss, Robert; Choukroun, Mathieu; Malaska, Michael J.
Abstract : The acetylene–ammonia co‐crystal exhibits significant anisotropic thermal expansion under conditions relevant to Saturn's icy moon Titan. The expansion is found to occur primarily along the c axis of the orthorhombic structure (about 2% extension over the temperature range 85–120 K). Abstract : Acetylene and ammonia are known to form a stable orthorhombic co‐crystal under the surface conditions of Saturn's moon Titan (1.5 bar = 150 kPa, 94 K). Such a material represents a potential new class of organic minerals that could play an important role in Titan's geology. In this work, the thermal expansion of this co‐crystalline system has been derived from in situ powder X‐ray diffraction data obtained between 85 and 120 K. The results indicate significant anisotropy, with the majority of the expansion occurring along the c axis (∼2% over the temperature range of interest). Rietveld refinements reveal little change to the structure compared with that previously reported by Boese, Bläser & Jansen [ J. Am. Chem. Soc. (2009), 131, 2104–2106]. The expansion is consistent with the alignment of C—H…N interactions along the chains in the a and b axes, and weak intermolecular bonding in the structural layers along the c axis.